(untitled) (World of finance, 2019)
Introduction. The dynamism of the integration processes, activation of mergers and acquisition processes, modernization of enterprises, development of new entrepreneurship forms, strengthening the international expansion of leading companies, the internationalization of capital is a characteristic features of the world economic development present stage. Creating different types of integrated structures becomes one of the effective ways enterprises adapt to the transformation processes, a prerequisite for organizational and economic preconditions for sustainable economic growth and competitiveness increasing of businesses - participants of integrated union. In present business environment of mergers and acquisitions (mergers&acquisitions, M&A) is one of the most important mechanisms for the rising value of enterprises, improving their activity effectiveness, risk diversification and optimization of investment portfolios by achieving a synergistic effect. Purpose. Development and substantiation of methodical approach due to the selection of companies based on synergetic merger (absorption), as a criteria for evaluating the effectiveness of the company value management and making recommendations for its practical application. Results. The author puts forth his conception of the improvement of the technique of the estimation of the synergy effect from mergers and acquisitions of companies. Conclusion. So, mergers and acquisitions of enterprises agreements have ample opportunities in term of the implementation of key strategic objectives and added value business. However, despite the high quantitative dynamics, in practice in most cases, the value still has not been created. This is primarily due to the inadequate estimates synergy effect and limited use of strategic opportunities to create added value in step of integration.